A three step one-pot regioselective synthesis of highly substituted pyrazolo[1,5-a]pyrimidines assisted by KHSO4 in aqueous media under ultrasound irradiation - Kaping, Shunan; Helissey, Philippe; Vishwakarma, Jai Narain (European Journal of Chemistry, 2020)
A simple and efficient synthesis of substituted pyrazolo[1,5-a]pyrimidine derivatives has been developed by the use of ultrasound. 5-Methyl-4-phenyl-1H-pyrazol-3-amine required for the synthesis of pyrazolo[1,5-a]pyrimidine derivatives has been easily obtained by the reaction of 3-(dimethylamino)-2-phenylacrylonitrile (formed from readily available 2-phenylacetonitrile) with hydrazine hydrate in refluxing ethanol. The 5-aminopyrazole was then reacted with various formylated active proton compounds in presence of KHSO4 in aqueous medium under ultrasound irradiation to give the desired products. The chemical structures of the newly synthesized compounds were confirmed by IR, 1H NMR, 13C NMR and Mass spectral data. X-ray crystallographic study of a selected compound 6-(4-chlorophenyl)-2-methyl-3-phenylpyrazolo[1,5-a]pyrimidin-7-amine (7c) was performed to ascertain the regioselectivity of the reaction. Crystal data for compound 7c: Triclinic, space group P-1 (no. 2), a = 8.0198(3) Å, b = 14.0341(6) Å, c = 14.2099(6) Å, α = 87.672(2)°, β = 83.902(2)°, γ = 89.120(2)°, V = 1588.87(11) Å3, Z = 4, T = 293(2) K, μ(MoKα) = 0.248 mm-1, Dcalc = 1.400 g/cm3, 12918 reflections measured (4.012° ≤ 2Θ ≤ 49°), 5152 unique (Rint = 0.0411, Rsigma = 0.0429) which were used in all calculations. The final R1 was 0.0486 (I > 2σ(I)) and wR2 was 0.1320 (all data).